Design and characterization of isothermal chambers filled with gradient-porous materials - Wang, Baicun (2019)
The concept of isothermal chambers filled with GPMs (gradient porous materials) was presented to homogenize the temperature distribution between the center and outer wall of the chambers with disc-shaped cross-section. An analytical heat transfer model was first developed to study the thermal behaviors of the GPMs chamber. Besides, numerical simulation was conducted to obtain the temperature profiles of the chamber with different GPMs. The effects of various gradient parameters on the heat resistance, temperature profiles and filling mass of the chamber were investigated in details. The results indicated that the gradient direction and gradient magnitude have a significant influence on the comprehensive thermal performances of the chamber filled with GPMs. Increasing the porosity gradient of GPMs along radius direction can effectively enhance the heat conduction. Moreover, the optimum gradient magnitude was obtained analytically to further improve the heat conduction of the GPMs chamber.